Transient Serotonin Syndrome by Concurrent Use of Electroconvulsive Therapy and Selective Serotonin Reuptake Inhibitor: A Case Report and Review of the Literature - Okamoto, Nagahisa; Sakamoto, Kota; Yamada, Maki (Case Reports in Psychiatry, 2012)
The serotonin syndrome, which is characterized by psychiatric, autonomic nervous and neurological symptoms, is considered to be caused by excessive stimulation of the 5-HT1A and 5-HT2 receptors in the gray matter and spinal cord of the central nervous system, after the start of dosing or increase of the dose of a serotoninergic drug. There have been hardly any reports of induction of serotonin syndrome by electroconvulsive therapy (ECT) in combination with antidepressant. We present the case of a female patient with major depressive disorder (MDD) who developed transient serotonin syndrome soon after the first session of ECT in combination with paroxetine. Paroxetine was discontinued, and her psychiatric, autonomic nervous and neurological symptoms were gradually relieved and disappeared within 2 days. We performed the second ECT session 5 days after the initial session and performed 12 sessions of ECT without any changes in the procedure of ECT and anesthesia, but no symptoms of SS were observed. Finally, her MDD remitted. ECT might cause transiently increased blood-brain barrier (BBB) permeability and enhance the transmissivity of the antidepressant in BBB. Therefore, it is necessary to pay attention to rare side effect of serotonin syndrome by ECT in combination with antidepressant.